Hunting in the Arctic and Alaska - Scull, Edward Marshall, 1880- (John C. Winston Co., 1914)
Account of author's hunting trips up the Yukon River, and to Chukotsk Peninsula; bear and walrus hunting in arctic seas; and trips up the Alaska and Kenai peninsulas.